1996
DOI: 10.1007/s004030050066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epidermal growth factor and transforming growth factor alpha on the function of wool follicles in culture

Abstract: The development of a procedure to culture wool follicles from Merino sheep in serum-free conditions has enabled us to investigate the actions of epidermal growth factor (EGF) and transforming growth factor alpha (TGF alpha) on follicle function, including fibre growth. Follicles grown in the absence of growth factors maintained their anagen morphology for 6 days as determined by light microscopy. During this time they incorporated [3H]thymidine into the DNA of the bulb matrix and outer root sheath (ORS) cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…In the present study, EGF treatment or overexpression of EGF accelerated the proliferation of the ORS cells. The mitogenic effect of EGF on the cultured ORS cells is consistent with previous studies [7,23]. In addition, EGF also promoted the migration of ORS cells.…”
Section: Egf Promotes Proliferation and Migration Of Ors Cellssupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, EGF treatment or overexpression of EGF accelerated the proliferation of the ORS cells. The mitogenic effect of EGF on the cultured ORS cells is consistent with previous studies [7,23]. In addition, EGF also promoted the migration of ORS cells.…”
Section: Egf Promotes Proliferation and Migration Of Ors Cellssupporting
confidence: 91%
“…These observations demonstrated a dynamic expression of EGFR during the initiation and cyclic growth of hair follicles, suggesting a spatiotemporal regulation of EGF signaling in follicle development and growth. Previous studies have shown that EGF can stimulate a mitogenic response in ORS cells in vitro and in vivo [6,7], yet the underlying mechanism remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with those described by Philpott and Kealey (1994) in human hair follicles with the response resembling the anagen-catagen transition described in sheep follicles (Panaretto et al, 1984). Responses to EGF in sheep wool follicles have been reported by Bond et al (1996) and Ansari-Renani and Hynd (2004). The data presented thus indicate concentration-dependent effects on mohair follicles and confirm, and taking into account the activity of mouse-derived growth factor, an apparent conservation of biological activity of EGF across species.…”
Section: Collection and Preparation Of Hair Folliclessupporting
confidence: 92%
“…Similar methodology has been successfully applied to investigations of sheep wool follicles (AnsariRenani and Hynd, 2004;Bond et al, 1996). This current study reviews selected results from the application of this in vitro technique in our research programmes that studied the chemical regulation and nutrition of pelage secondary hair follicles from major fibre-bearing ruminant animal species.…”
Section: Introductionmentioning
confidence: 95%
“…In order to investigate and understand the mechanisms involved in the control of keratin gene expression, in vitro experimental systems are required. Culture systems for intact wool 4 –6 and hair follicles have been successfully established 7 –9 . Although human and rat germinative/matrix cell culture systems have been reported, 10 –13 there have been no previous reports of wool follicle matrix cell culture.…”
mentioning
confidence: 99%